THE VERTICAL CITY: APPROACHES TO THE SKYSCRAPER CITY AS PHENOMENOLOGICAL SPACE AND SEMANTIC FIELD - Troelsen, Anders (The Nordic Journal of Aesthetics, 2020)
The article is a kind of “project essay” or “brain storm” concerning skyscraper cities. It proposes different approaches for the study of this subject. Starting with the observation that in Danish traditional houses are lying (ligger), whereas skyscrapers are “standing” (står), different phenomenological and discursive perspectives for the study are sketched. The article also suggests that the analysis of contemporary skyscraper cities can shed new light on more traditional cities in the same way as new media illuminate the characterics of old media.